Kajian stilistika dalam antologi puisi negeri dongeng karya mahasiswa universitas peradaban - Farkhatin, Lilis; Purnama, Wulan; Irma, Cintya Nurika (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2020)
Stylistics is basically the activity of writers using language, especially language that triggers creativity to sort out the use of language. In this research using the study of stylistics in the poetry anthology of "Negeri Dongeng" by the students of Peradaban University. This research is a qualitative descriptive study. The data in this study are descriptive words in the Poetry Anthology of "Negeri Dongeng" by Indonesian Language and Literature Education Students at the Peradaban UniversityÂ  and reference books related to research. Data collection techniques with document analysis that starts from the stages of reading, recording, and analyzing data in the Anthology Poem "Negeri Dongeng". The data validity technique in this research is data triangulation. The purpose of this research is to explain the study of stylistics in the anthology of "Negeri Dongeng" poetry by Peradaban UniversityÂ  Students. The results of this study are to explain 6 problems regarding the use of sound style, word style, sentence style, discourse style, the existence of figurative language in the use of figurative language types: metaphor, personification, paradox, hyperbole. While the use of images, namely: vision, hearing, smell, motion, touch. Which is dominated by figurative language imagery.